Cover Picture: Macromol. Mater. Eng. 6/2015. Issue 6 (June 2015) - Larrañeta, Eneko; Lutton, Rebecca E. M.; Brady, Aaron J.; Vicente‐Pérez, Eva M.; Woolfson, A. David; Thakur, Raghu Raj Singh; Donnelly, Ryan F.
<x xml:space="preserve">Abstract</x> Front Cover: Microwave radiation is used to crosslink poly(methyl vinyl ether‐alt‐maleic acid) and poly(ethylene glycol) mixtures yielding hydrogels. The crosslinking process is implemented in the production of hydrogel‐forming microneedle arrays for transdermal drug delivery. The cover shows the crosslinking reaction between the two polymers and the transdermal permeation mechanism of the resulting hydrogel‐forming microneedle arrays after skin insertion. Further details can be found in the article by E. Larrañeta, R. E. M. Lutton, A. J. Brady, E. M. Vicente‐Pérez, A. D. Woolfson, R. R. S. Thakur, and R. F. Donnelly* on page 586.